Can Muscle Relaxation Affect Balance in Patients with Tension-Type Headache? A Pre-Post Study - Zahra Rojhani-Shirazi; Ali Barzegar; ElhamNouraddini; NegarAjdari; Marzieh Mohamadi (Shiraz University of Medical Sciences, 2017)
Background: Proprioceptive inputs from the cervical region play an important role in balance. In patients with tension-type headache (TTH), proprioception is altered. The effect of treatment for TTH on balance is unclear. The aim of this study was to evaluate the effectiveness of post-isometric relaxation (PIR) in the neck muscles on pain, disability and balance in patients with TTH. Methods: 30 patients with chronic TTH who had a trigger point and tenderness in the upper trapezius, sternocleidomastoid (SCM), suboccipital or splenius muscles were enrolled in the study. The patients underwent PIR based on Liebenson's method. Before and after treatment, balance was evaluated with the Y balance test, time up and go test, functional reach test and single leg stance test. As clinical symptoms of TTH we considered the intensity and frequency of headaches,which were recorded along with neck disability index (NDI) as secondary outcomes. Paired t-tests were used to analyze the data. Results: The results of the Y balance test, time up and go test, functional reach test and single leg stance test changed significantly after treatment (P<0.001). Significant differences were also found for all secondary variables (P<0.001). Conclusion: The results of this study showed that the PIR technique for muscle relaxation in the upper trapezius, SCM, suboccipital or splenius muscles may improve balance along with clinical symptoms such as pain and disability in patients with TTH.